α-Hispanolol Induces Apoptosis and Suppresses Migration and Invasion of Glioblastoma Cells Likely via Downregulation of MMP-2/9 Expression and p38MAPK Attenuation - Sánchez-Martín, Vanesa; Jiménez-García, Lidia; Herranz, Sandra; Luque, Alfonso; Acebo, Paloma; Amesty, Ángel; Estévez-Braun, Ana; de las Heras, Beatriz; Hortelano, Sonsoles (Frontiers in Pharmacology, 2019)
α-hispanolol (α-H) is a labdane diterpenoid that has been shown to induce apoptosis in several human cancer cells. However, the effect of α-H in human glioblastoma cells has not been described. In the present work, we have investigated the effects of α-H on apoptosis, migration and invasion of human glioblastoma cells with the aim of identifying the molecular targets underlying its mechanism of action. The results revealed that α-H showed significant cytotoxicity against human glioma cancer cell lines U87 and U373 in a concentration- and time-dependent manner. This effect was higher in U87 cells and linked to apoptosis, as revealed the increased percentage of sub-G1 population by cell cycle analysis and acquisition of typical features of apoptotic cell morphology. Apoptosis was also confirmed by significant presence of Annexin V positive cells and caspase activation. Pretreatment with caspase inhibitors diminishes the activities of caspase 8, 9, and 3 and maintains the percentage of viable glioblastoma cells, indicating that α-H induced cell apoptosis through both the extrinsic and the intrinsic pathways. Moreover, we also found that α-H down-regulated the anti-apoptotic Bcl-2 and Bcl-xL proteins, and activated the pro-apoptotic Bid and Bax proteins. On the other hand, α-H exhibited inhibitory effects on the migration and invasion of U87 cells in a concentration-dependent manner. Furthermore, additional experiments showed that α-H treatment reduced the enzymatic activities and protein levels of matrix metalloproteinase MMP-2 and MMP-9 and increased the expression of TIMP-1 inhibitor, probably via p38MAPK regulation. Finally, xenografts assays confirmed the anti-glioma efficacy of α-H. Taken together, these findings suggest that α-H may exert anti-tumoral effects in vitro and in vivo through the inhibition of cell proliferation and invasion as well as by the induction of apoptosis in human glioblastoma cells. This research describes α-H as a new drug which may improve the therapeutic efficacy against glioblastoma tumors.